2016
DOI: 10.1270/jsbbs.16014
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding and evaluation of both a foreign <i>Bacillus thuringiensis</i> and a <i>Lysine-rich protein</i> gene in the elite <i>indica</i> rice 9311

Abstract: Gene pyramiding is an efficient approach for the genetic improvement of multiple agronomic traits simultaneously. In this study, we pyramided two foreign genes, cry1Ac driven by the rice Actin I promoter, and lysine-rich protein (LRP), driven by the endosperm-specific GLUTELIN1 (GT1) promoter, into the elite indica cultivar 9311. These two genes were chosen in an attempt to enhance insect-resistance and Lysine (Lys) content. In the pyramided line, the foreign gene cry1Ac was efficiently expressed in the leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…In the past decades, many studies on genetic engineering of plant disease resistance, drought resistance, and salt tolerance have been reported [42,44,46,47]. Also, using genetic engineering methods to develop food crops with increased contents of specific micronutrients and phytonutrients such as high-zinc rice, provitamin A-enriched maize, and anthocyanin-enriched “Purple Tomatoes’’, have been well developed [36,41].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, many studies on genetic engineering of plant disease resistance, drought resistance, and salt tolerance have been reported [42,44,46,47]. Also, using genetic engineering methods to develop food crops with increased contents of specific micronutrients and phytonutrients such as high-zinc rice, provitamin A-enriched maize, and anthocyanin-enriched “Purple Tomatoes’’, have been well developed [36,41].…”
Section: Discussionmentioning
confidence: 99%
“…During the tillering period, an artificial infestation was introduced from July 7 to 8, 2014. The density of infestation was 2 seedlings with one worm, which is according to the standard of the International Rice Research Institute ( Pathak et al, 1971 ) and Zhou’s methods (1985). The primary hatching larvae were inoculated into the ligule between the stem and the second or third leaf sheath.…”
Section: Methodsmentioning
confidence: 99%
“…The damage index was calculated by the following formula: Damage index = dead heart rate/dead heart rate of control. The resistance levels of rice cultivars are determined according to Pathak et al (1971) and are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Molecular marker technology assists the breeding process because pyramiding genes can speed up selection cycles process (Lan and Chao, 2011). Phenotypic and molecular markers evaluation for gene pyramiding in rice has been conducted for bacterial leaf blight (Chukwu et al, 2019), eight grain yield-related QTLs (quantitative trait loci; Zong et al, 2012), cry1Ac (insect resistance) and lysine rich protein (Liu et al, 2016), blast, bacterial blight and BPH resistance genes in restorer lines (Ji et al, 2016). Meanwhile, just recently QTLs for salinity, drought and submergence have been successfully pyramided into cv.…”
Section: Introductionmentioning
confidence: 99%